Roles and Student Identities in Online Large Course Forums: Implications for Practice - Baxter, Jacqueline Aundree; Haycock, Jo (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
The use of large online discussion forums within online and distance learning continues to grow. Recent innovations in online learning such as the MOOC (massive open online course) and concomitant growth in the use of online media for the delivery of courses in traditional campus based universities provide both opportunity and challenge for online tutors and learners alike. The recognition of the role that online tutors and student identity plays in the field of retention and progression of distance learners is also well documented in the field of distance learning. Focusing on a course forum linked to a single Level 2 undergraduate module and open to over 1,000 students, this ideographic case study, set in a large distance learning university, uses qualitative methodology to examine the extent to which participation in a large forum can be considered within community of practice (COP) frameworks and contributes to feelings of efficacy, student identity, and motivation. The paper draws on current theory pertaining to online communities and examines this in relation to the extent to which the forum adds to feelings of academic and social integration. The study concludes that although the large forum environment facilitates a certain degree of academic integration and identity there is evidence that it also presents a number of barriers producing negative effects on student motivation and online identity.